2008
DOI: 10.2298/sarh0808423j
|View full text |Cite
|
Sign up to set email alerts
|

The role of cytokine in regulation of the natural killer cell activity

Abstract: Natural killer (NK) cells are characterized by a CD3-CD16+ CD56+ immunophenotype and have a central role in the innate immune system. They are defined by their capacity to kill certain tumour-target cells or virus infected cells without prior sensitization or MHC-restriction.The activity of the NK cells is determined by the balance between activation and inhibitory receptor molecules expressed on the surface of NK cells. However, several cytokines and chemokines can significantly modulate their activity, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…31 Accumulating evidence has pointed to a critical role for Tregs in reducing the immune responses of NK cells. Findings showed that Tregs suppress NK cell effector functions both in vitro and in vivo, thus inhibiting homeostatic proliferation, cytotoxicity, and IFN-g production.…”
Section: Discussionmentioning
confidence: 99%
“…31 Accumulating evidence has pointed to a critical role for Tregs in reducing the immune responses of NK cells. Findings showed that Tregs suppress NK cell effector functions both in vitro and in vivo, thus inhibiting homeostatic proliferation, cytotoxicity, and IFN-g production.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulation mediated by NK cells is very important mechanism in tumor immunity, as well as in other immunodepressions of the immune system. TNF- alpha induces cell apoptosis and immune reactions [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has recently been shown that pregnancy alters the equilibrium of cytokines towards the Th2 and away from the Th1 pattern during the antiparasite response in pregnant mice (T cell-mediated immune-response patterns, Th1 secreting IL-2, INF-g, and TNF-b, and Th2 secreting IL-4, IL-5, IL-6, IL-9, IL-10, and IL-13, identified among mouse CD4 Th clones) [7,8,10]. This shift in cytokine pattern provides an explanation for the increased susceptibility to Leishmania infection in pregnant mice, and possibly in pregnant women, as was the case with our patient [7,9].…”
Section: Discussionmentioning
confidence: 99%